Validitas dan Efektivitas Petunjuk Praktikum Elektronik Keanekaragaman Hayati untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SMA - Satmaka, Alfany Abied Maulana; Rohman, Fatchur; Prabaningtyas, Sitoresmi (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Increasingly tight competition in the 21st century requires students to be able to think well. Students are required to have critical thinking to be able to compete superiorly in increasingly fierce competition in the 21st century. One innovation in biodiversity learning that can be adopted is the development of electronic biodiversity practicum instructions in inquiry learning. The development procedure used consists of five stages, including: 1) assessment/analysis which consists of two phases, namely needs assessment and front-end analysis; 2) design (design); 3) development (development); 4) implementation (implementation); and 5) evaluation. Biodiversity electronic practicum instructions after being validated have very valid validity and are effective in improving critical thinking skills.